iBoccia: monitoring elderly while playing Boccia gameplay - Figueira, Carina (2017)
The size of the aging population has been increasing over the last years, leading to a search for solutions that can increase the quality of life of the elderlies. One of the main means of action is focused on their physical activity. A non-sedentary life can help in disease prevention and disability reduction, leading to an independent living with quality. Moreover, the practice of physical exercise can decrease fall risks and its consequences. Furthermore, it is desirable that the solutions can be accessed by anyone, with a low inherent cost. The Boccia game is a good way to promote physical activity to the elderly, due to its simplicity and easy adaptability to the physical limitations of the elderly. Following this trend, this paper presents iBoccia, a novel framework to monitor elderly while playing Boccia game, through wearable sensors, Mio Fuse band and pandlet (inertial sensor), and a non-wearable device, Kinect camera. Several performance metrics are expected to be measured during the gameplay. Using the pandlet we calculate wrist rotation angles and force applied during ball throw, using the Kinect we recognize facial expressions and from the Mio Fuse band we retrieve heart rate.